Effects of frugivore impoverishment and seed predators on the recruitment of a keystone palm - Fadini, Rodrigo F. [UNESP]; Fleury, Marina [UNESP]; Donatti, Camila I.; Galetti, Mauro [UNESP] (Gauthier-villars/editions Elsevier, 2009)
Many plant species are threatened as a result of extinction of their large-bodied frugivores all over the world. Additionally, introduced herbivores and seed predators may cause severe pressure on early stages of plant recruitment. We studied the seed dispersal and seed predation of the keystone palm Euterpe edulis on a land-bridge island with a highly impoverished frugivore fauna and overabundant seed predators, and in a continuous Atlantic forest in Brazil. While the diversity of avian seed dispersers and predators was higher on the mainland, the abundance of seed dispersers was 4-fold higher on the island. Turdus flavipes was responsible for 72% and 96% of seeds removed in the island and mainland, respectively. However, the higher density of T. flaviceps on the island did not result in higher seed removal. In fact, seed removal rate was 1.7 times lower there than on the mainland, probably due to the aggressive behavior of the major seed disperser who defend palm fruits. Seed predation, on the other hand, was markedly higher on the island, where nearly 100% of seeds were preyed upon, but only 0.3% on the mainland. As a consequence of higher seed predation the population of E. edulis has few numbers of seedlings and saplings on the island. Therefore, management of the seed predator populations on the island is a key priority for recovering the natural population of this keystone palm and the frugivores that depend on its fruits. (C) 2008 Elsevier Masson SAS. All rights reserved.
Keywords: Anchieta Island; Defaunation; Frugivory; Recruitment bottlenecks; Turdus